Flood risk management in New Zealand: A case study of the Northland urban community - Auliagisni W; Wilkinson S; Elkharboutly M (IOP Publishing Ltd, 2022)
The Northland river is characterised by having a short stream and large catchments. Heavy rains in the region trigger the rapid rise of the water levels and causes flooding, affecting the urban community in the flood plain with flash floods and river overflow as double threats. The government-initiated programs to protect urban communities such as 'predict and mitigate' but primarily focuses on physical infrastructure protection. While providing infrastructure is beneficial, developing a resilient community comprises more holistic strategies. There is a need for improving the local capacity to enhance resilience. A resilient, human-focused mitigation strategy which includes the affected communities, as well as the existing infrastructure, can reduce flood risks more efficiently. This paper explores the ways the Northland communities follow to mitigate existing flood risks, including their perceptions of the current flood protection strategies. This study investigates also the social and cultural elements that influence responses to flood risks. The main recommendation, of the study advocates a community-based risk management plan to complement the government's strategy to efficiently mitigate flood risk in the urban Northland.